A three-tiered architectural model for Digital Twins in Education - Martins, Valéria Farinazzo; Bachmann, João Eduardo Cosentino; Cardoso, Alexandre; Silveira, Ismar Frango (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS), 2024)
The advent of Digital Twins, integrating technologies such as Mixed Reality, the Internet of Things, Machine Learning, Big Data, and Cloud Computing, is increasingly demonstrating its potential across various domains. These technologies enable the creation of accurate simulations of real objects, processes, and systems based on real-time data. This capability supports a wide range of applications, including hypothesis testing, design and prototyping, process optimization, among others, which makes this solution strongly suitable to applications in education, training and skills development. To effectively implement Digital Twins in the educational context, this paper proposes a three-tiered software architecture, comprising a Data Acquisition Tier, another tier for Processing and Analysis and the last one for Visualization and Interaction. The paper finishes presenting a case for technical training in an energy provider company.